2022
DOI: 10.1096/fj.202100717rr
|View full text |Cite
|
Sign up to set email alerts
|

Beta adrenergic receptor antagonist can modify Pseudomonas aeruginosa biofilm formation in vitro: Implications for chronic wounds

Abstract: Non-healing wounds are a major medical challenge, affecting over 6.5 million people in the US alone, with associated healthcare costs of about $16 billion annually. They can result in prolonged hospitalizations, work loss, disability, poor quality of life, and in diabetic patients with foot ulcers, amputation of the affected limb in 25% of patients. Though chronic ulcers may arise from different underlying diseases, the unifying feature is chronic infection, driving persistent inflammation that prolongs the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…25−30 The ability of β-adrenoreceptor antagonists or blockers to inhibit the QS system has been demonstrated by previous studies. 13,14,31 However, the target of QS suppression was not been identified.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25−30 The ability of β-adrenoreceptor antagonists or blockers to inhibit the QS system has been demonstrated by previous studies. 13,14,31 However, the target of QS suppression was not been identified.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Dronedarone blocks potassium, sodium, and L-type calcium currents and exerts antiadrenergic effects by noncompetitive binding to β-adrenergic receptors . However, when nonantibiotic drugs are used as antibiotic potentiators, their mechanisms of action are usually different from their original pharmacological effects. The ability of β-adrenoreceptor antagonists or blockers to inhibit the QS system has been demonstrated by previous studies. ,, However, the target of QS suppression was not been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that catecholamines increase the number of Pseudomonas aeruginosa after antibiotic therapy 85 . P. aeruginosa , the most commonly colonized bacterium in skin wounds, is inhibited by β‐blockers leading to a decrease in biofilm formation 86 . Bacterial AR exposed to stress hormones can also alter their gene expression to adapt to the injury environment for long‐term survival 87 .…”
Section: Regulation Mechanism Of β‐Blockers In Soft Tissue Wound Heal...mentioning
confidence: 99%
“…85 P. aeruginosa, the most commonly colonized bacterium in skin wounds, is inhibited by β-blockers leading to a decrease in biofilm formation. 86 Bacterial AR exposed to stress hormones can also alter their gene expression to adapt to the injury environment for long-term survival. 87 Therefore, β-blockers exert an anti-virulence effect, while inhibiting the QS, hence playing a role in preventing infection and promoting wound healing.…”
Section: β-Blockers Modulate Bacterial Virulencementioning
confidence: 99%